5+6t=10-7

Simple and best practice solution for 5+6t=10-7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5+6t=10-7 equation:


Simplifying
5 + 6t = 10 + -7

Combine like terms: 10 + -7 = 3
5 + 6t = 3

Solving
5 + 6t = 3

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 6t = 3 + -5

Combine like terms: 5 + -5 = 0
0 + 6t = 3 + -5
6t = 3 + -5

Combine like terms: 3 + -5 = -2
6t = -2

Divide each side by '6'.
t = -0.3333333333

Simplifying
t = -0.3333333333

See similar equations:

| 36x-96= | | 3x-4=5x-24 | | 1/3n-6=15 | | 30*365= | | 32x=16x^2 | | tan^2+4tan+2=0 | | 9-4n=7 | | 8m-25=30 | | 3x-4+10x-48=180 | | 3x-(x-(x-3))=-1 | | 3x-4+5x-12=180 | | (252)1/5 | | 8(t-4)+4t=4(3t+5)-10 | | 10(x-1)+4=12x | | 3*x-7=4*4+2 | | 8-2(t+5)=-2t-2 | | 3x/2-(x-1)/3=x/6 | | 6t+26=19t | | 3(y-7)=4(4+2) | | 8-2(t+5)= | | .2(x+3)-.5(x+3)=-.3x-.9 | | (5x-7)=(4x-6) | | 9x-2(2x+3)=x-4 | | -4(-9+x)=8 | | 2x-3(-2x+4)=13+x | | 2lnx=ln(10-3x) | | 3y+-8=y | | 5x^2-25=20x | | -3(6x+7)=-57 | | -5+0.5a=4 | | -3x+25=76 | | 11x-1/4 |

Equations solver categories